Novel staging classification of primary mitral regurgitation based on the presence of cardiac damage. (25th November 2020) - Van Wijngaarden, A.L; Hiemstra, Y.L; Van Der Bijl, P; Delgado, V; Ajmone Marsan, N; Bax, J.J
Abstract: Background: The indication for surgery in patients with severe primary mitral regurgitation (MR) is currently based on the presence of symptoms, left ventricular (LV) dilatation and dysfunction, atrial fibrillation and pulmonary hypertension. The aim of this study was to evaluate the prognostic impact of a new staging classification based on cardiac damage including the known risk factors but also including global longitudinal strain (GLS), severe left atrial (LA) dilatation and right ventricular (RV) dysfunction. Methods: In total 614 patients who underwent surgery for severe primary MR with available baseline transthoracic echocardiograms were included. Patients were classified according to the extent of cardiac damage (Figure): Stage 0-no cardiac damage, Stage 1-LV damage, Stage 2-LA damage, Stage 3-pulmonary vasculature or tricuspid valve damage and Stage 4-RV damage. Patients were followed for all-cause mortality. Results: Based on the proposed classification, 172 (28%) patients were classified as Stage 0, 102 (17%) as Stage 1, 134 (21%) as Stage 2, 135 (22%) as Stage 3 and 71 (11%) as Stage 4. The more advanced the stage, the older the patients were with worse kidney function, more symptoms and higher EuroScore. Kaplan-Meier curve analysis revealed that patients with more advanced stages of cardiac damage had a significantly worse survival (log-rank chi-square 35.2; p<0.001) (Figure). On multivariable analysis, age, male, chronic obstructive pulmonary disease, kidney function, and stage of cardiac damage were independently associated with all-cause mortality. For each stage increase, a 22% higher risk for all-cause mortality was observed (95% CI: 1.064–1.395; p=0.004). Conclusion: In patients with severe primary MR, a novel staging classification based on the extent of cardiac damage, may help refining risk stratification, particularly including also GLS, LA dilatation and RV dysfunction in the assessment. Funding Acknowledgement: Type of funding source: None